Septo-Optic Dysplasia Diagnosed in a Newborn Infant with Normoglycemia: The Importance of Thorough Physical Examination - Aishwarya Palorath; Ishita Kharode (Case Reports in Pediatrics)
A newborn male infant was admitted to the neonatal intensive care unit due to suspected sepsis. He was clinically stable with normal electrolyte levels on admission. However, he was noted to have micropenis and bilateral nonpalpable testes. Ultrasound imaging confirmed the presence of both gonads in the inguinal canal, with no Müllerian structures visualized. Laboratory examination revealed an undetectable random plasma cortisol level; subsequent ACTH stimulation testing confirmed adrenal insufficiency. Further testing revealed additional pituitary hormone deficiencies, and the infant was started on multiple hormone replacement therapies. Magnetic resonance imaging identified absent septum pellucidum, pointing of the frontal horns, and optic nerve hypoplasia. A diagnosis of septo-optic dysplasia was made based on this combination of findings. This case highlights the importance of thorough physical examination in newborn infants, which may reveal the only sign of underlying pathology in the absence of other concerning findings.